A dose finding clinical trial of cabozantinib (XL184) administered in combination with abiraterone acetate in metastatic castration‐resistant prostate cancer. Issue 14 (7th June 2018) - Choudhury, Atish D.; Gray, Kathryn P.; Supko, Jeffrey G.; Harshman, Lauren C.; Taplin, Mary‐Ellen; Pace, Amanda F.; Farina, Matthew; Zukotynski, Katherine A.; Bernard, Brandon; Kantoff, Philip W.; Pomerantz, Mark; Sweeney, Christopher
Abstract : Background: Cabozantinib can enhance the effect of abiraterone in preclinical prostate cancer models. This study aimed to define the recommended phase 2 dose (RP2D) and preliminary efficacy of abiraterone + cabozantinib in mCRPC. Methods: Patients with progressive mCRPC with 0‐2 prior chemotherapy regimens but no prior CYP17A1 or MET inhibitor received abiraterone acetate at 1000 mg daily with prednisone 5 mg BID in combination with cabozantinib at 20, 40, or 60 mg daily in a dose‐escalation 3 + 3 open‐label phase 1 design (Part A). After tolerable doses were defined, cohorts were expanded to better define toxicity and efficacy (Part B). Results: There were no dose‐limiting toxicities (DLTs) in the first 4 weeks at any of the three dose levels in Part A. Two of the three patients at the 60 mg dose level required dose reductions beyond cycle 2 due to fatigue. In Part B, nine more patients were accrued to each of the 20 and 40 mg doses. Of the 12 patients treated at the 40 mg dose, only one DLT (grade 3 Lipase elevation) was observed in cycle 1. The median time to radiographic progression was 12.88 months (95% CI:5.42‐ not estimated [NE]) in the 20 mg cohort and 22.01 months (95% CI:15.44‐NE) in the 40 mg cohort. Median overall survival was 23.29 months (95% CI:19.06‐NE) in the 20 mg cohort and 39.08 months (95% CI:17.38‐NE) in the 40 mg cohort. Conclusions: Based on tolerability and preliminary efficacy, 40 mg cabozantinib plus 1000 mg abiraterone daily is the RP2D.